Colecalciferol Initiation Post Minimal Trauma Fracture - Nguyen, Van T. (Hosp Pharm, 2018)
Purpose: The purpose of this study was to determine the proportion of patients admitted to a major tertiary teaching hospital in Australia aged 50 years and older with a confirmed neck of femur or vertebral minimal trauma fracture, who are commenced on colecalciferol supplementation by discharge, and to describe the doses prescribed. Methods: A subanalysis of a retrospective audit of electronic medical files for patients admitted with a minimal trauma fracture of the hip or vertebra between January 1, 2016, and June 30, 2016, was conducted. Results: A total of 406 patients were screened and 64 patients were included in the audit. In this subanalysis of these 64 patients eligible for inclusion, 38 were not on any vitamin or mineral supplementation at admission. Of these, 26 patients (68.4%) had their serum colecalciferol levels measured, and 21 patients (55.2%) overall were initiated on colecalciferol. Conclusion: Over half of patients with a minimal trauma fracture were commenced on colecalciferol therapy, but a noteworthy proportion of patients remain untreated. Patients with colecalciferol levels are more likely to be initiated on therapy compared with those of whom levels were not taken during admission. This is a missed opportunity for intervention that may place patients at a higher risk of subsequent fracture; therefore, effective strategies should be implemented to address this treatment gap in the future.